Causal Model of Mathematical Competences in Kinderegarten - Tepeš, Božidar (Array, 2014)
In this paper, the authors defined mathematical competences for kindergarten children. Mathematical competences were grouped in following areas: language/data, geometry and arithmetic. Statistical set for the research consisted of 77 children from the kindergarten in Zagreb, Croatia. Authors had 19 measuring variables together with the evaluated results of described tasks. Methods for causal modelling were described in three steps. Results were analysed in three causal models for language/data, geometry, and arithmetic. Causal models were represented in three directed acyclic graphs. Authors analysed these three causal models and gave critical views of the research.